Enhancing Security and Privacy of Patient Data in Healthcare: A SmartPLS Analysis of Blockchain Technology Implementation - Indri Handayani; Desy Apriani; Mulyati Mulyati; Achani Rahmania Az Zahra; Natasya Aprila Yusuf (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
Security and privacy of patient data are critical concerns in the healthcare system. This research aims to investigate the impact of implementing blockchain technology on enhancing the security and privacy of patient data in healthcare. Using the SmartPLS analysis method, this study empirically examines the relationships between blockchain technology implementation and data security and data privacy within the healthcare system. The research sample consists of healthcare organizations that have implemented blockchain technology for data management. Data is collected through surveys and analyzed using SmartPLS to assess the effects of blockchain technology on data security and privacy. The findings reveal the positive influence of blockchain technology implementation on enhancing the security and privacy of patient data. The study also identifies challenges, such as scalability and interoperability, that need to be addressed for successful implementation. This research contributes to the existing literature by providing empirical evidence on the benefits and challenges of implementing blockchain technology to safeguard patient data in healthcare systems.